Peran Mediasi Kepuasan Kerja Atas Hubungan Etika Kerja Islam dan Kinerja Karyawan Pada RS PKU Muhammadiyah Surakarta - Zumrotul Riza Muthoharoh (Relevance: Journal of Management and Business, 2018)
ABSTRACTThis research addreses to determinate the effect of Islamic work ethics to employee performance and job satisfaction as an intervening variable in RS PKU Muhammadiyah Surakarta.The population in this study are all nurses RS PKU Muhammadiyah Surakarta totaling 258 nurses. The sampling tehnique used purposive sampling method and sample obtained 75 respondents. Data were analyzed using SPSS for Windows Release 20.0.The dependent variable (Y) of this research is employee performance. The independent variable (X) Islamic work ethic and for intervening variables (Z) is job satisfaction. This method used is quantitative research methods. For the method of data analysis self are using path analysis.The results of this showed that: (1) the work ethic Islam is influence positively significant for the employee performance. (2) Islamic work ethics influenced positively significant effect on job satisfaction. (3) Job satisfaction has a positively significant on employee performance. (4) The Islamic work ethic influenced toward employee performance by means job satisfaction as intervening variable.Keywords: Islamic work ethic, job satisfaction, employee performance